2013
DOI: 10.3354/meps10308
|View full text |Cite
|
Sign up to set email alerts
|

Population growth across heterogeneous environments: effects of harvesting and age structure

Abstract: Population growth is affected by several factors such as climate, species interaction and harvesting pressure. However, additional complexity can arise if fishing increases the sensitivity to environmental variability. To predict the effects of fisheries and climate on marine populations, there is a need for improved understanding of how they affect key ecological processes such as population growth. In this study, we used a comparative approach investigating commercially fished species across different ecosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Note that following the methods used, if the elasticity to recruitment increases, the elasticity to survival decreases, and vice versa. However, transient elasticity does not tell us how much and Gulf of Alaska (GOA) pollock Theragra chalcogramma stocks, North Sea (NS) cod stock, northern Atlantic (NA), southern Atlantic (SA) and Balearic Islands (BI) hake Merluccius merluccius stocks are from Durant et al (2013) the population is actually changing, but it helps us to understand the processes underlying these changes. In our study, the pre-eminent factor is the negative association between the generation time μ and the transient elasticity to recruitment, confirming a previous study conducted on other data for gadoids only ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that following the methods used, if the elasticity to recruitment increases, the elasticity to survival decreases, and vice versa. However, transient elasticity does not tell us how much and Gulf of Alaska (GOA) pollock Theragra chalcogramma stocks, North Sea (NS) cod stock, northern Atlantic (NA), southern Atlantic (SA) and Balearic Islands (BI) hake Merluccius merluccius stocks are from Durant et al (2013) the population is actually changing, but it helps us to understand the processes underlying these changes. In our study, the pre-eminent factor is the negative association between the generation time μ and the transient elasticity to recruitment, confirming a previous study conducted on other data for gadoids only ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate how recruitment affects spawning stock biomass and population numbers, we performed an analysis of transient elasticity to recruitment variation (hereafter called elasticity e; e being the contribution of recruitment or survival to population growth changes) following the principles defined by Caswell (2007) and methods described by Durant et al (2013). We used numerical methods based on simulating the population from year t to year t + t g .…”
Section: Calculation Of Population Growth and Elasticitymentioning
confidence: 99%
“…Durant et al (2013) showed that the contribution of recruitment to population growth was affected by environmental conditions and by the age-structure of the population. However, contrary to what was expected, Ottersen et al (2013) found little or no general decrease in mean age in the spawning stock.…”
Section: Discussionmentioning
confidence: 99%
“…Juvenation may increase a populations' ability to directly respond to environmental fluctuations (Rouyer et al 2011), emphasizing the importance of the interaction between fisheries, environment, and recruitment and population growth that produces complex synergic effects on the population dynamics of marine species. Durant et al (2013, this Theme Section) explored how external forcing (climate and fishing) and recruitment modulate the population dynamics of fish within different environments. They calculated the realized yearly population growth rate of 7 gadoid stocks across different ecosystems.…”
Section: (5) Population Growth Rate Across Heterogeneous Environmentsmentioning
confidence: 99%
See 1 more Smart Citation